Antworten auf Ergänzungsfragen im Deutschen und Polnischen - Prokop, Izabela (Studia Germanica Posnaniensia, 2018)
The article - a contribution to contrastive syntactic studies, discusses the possible structural variants of the answers to the wh-(nominal and adverbial) questions in German and relates to them their equivalents in Polish. The replicas were divided from the point of view of semantics (according to types of questions), structure (into developed and elliptical ones) and according to the pragmatic criteria (into direct, indirect, and evasive ones).